A Literature Review of Pharmacologic Acute and Preventive Treatment for Migraine in Children and Adolescents - Richard, Richard; Erick, Erick (The Indonesian Journal of General Medicine, 2024)
Background: The literature on pharmacologic and non-pharmacologic treatments for migraine in children and adolescents highlights the complexity of managing this condition in a pediatric population. Literature Review: The management of acute migraine pain in pediatric patients necessitates individualized treatment plans that account for the unique pharmacokinetics and pharmacodynamics of medications in this age group. While paracetamol and ibuprofen are effective first-line treatments, some migraine episodes may remain refractory to these analgesics, indicating the need for alternative therapeutic options, such as triptans, despite their limited use in children. Conclusion: In conclusion, the current literature emphasizes the need for a multifaceted approach to migraine management in children and adolescents, integrating both pharmacologic and non-pharmacologic strategies. The limitations of existing pharmacological treatments, coupled with the promising results of non-pharmacological interventions, suggest that future research should focus on developing individualized treatment plans that address the unique needs of this population.